Perancangan Aplikasi Mobile Pembukuan Pengadaan Kayu Bangsal Delima Jambi Berbasis Android - Yudhistira, Reynaldi; Gunardi; Nugroho , Agus (LPPM Universitas Dinamika Bangsa, 2024)
This research is motivated by the absence of a bookkeeping application that can be accessed anywhere by the owner of the Jambi Delima Ward. This is because the bookkeeping system is manual and cannot be carried anywhere. The purpose of this research is to design a bookkeeping application for owners using mobile. The system development method used is data collection and interviews and also uses the waterfall method using modeling tools use case diagrams, activity diagrams, class diagrams, and flowcharts. The software used is Android Studio and Firebase. With the design of this mobile application can be accessed anywhere and anytime